2012
DOI: 10.1007/s11999-012-2506-1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Pain and Function After Labral Reconstruction During Femoroacetabular Impingement Surgery

Abstract: Background Labral refixation rather than resection provides better pain relief and function after femoroacetabular impingement (FAI) surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 11 publications
4
51
0
Order By: Relevance
“…This way, patients become extremely fearful of re-injury or specific activities that have been associated in their mind with pain or re-injury risk. A model that is known as the "fear -avoidance model" [25][26][27][28] .…”
Section: Etiology Of Fear Of Re-injurymentioning
confidence: 99%
“…This way, patients become extremely fearful of re-injury or specific activities that have been associated in their mind with pain or re-injury risk. A model that is known as the "fear -avoidance model" [25][26][27][28] .…”
Section: Etiology Of Fear Of Re-injurymentioning
confidence: 99%
“…5 Likewise, good results have been reported for labrum reconstruction using ligamentum teres capitis or fascia lata autograft in patients undergoing open surgical hip dislocation. 13 In this study, the investigators reported on 19 patients (20 hips) with a minimum follow-up of 12 months. Three patients were converted to total hip arthroplasty within 36 months of the primary surgical In regard to the graft source, the first description of this technique used ligamentum teres capitis autograft in an open surgical hip dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Several other recent studies have added to the literature supporting the ability of labral reconstruction in appropriately selected patients to improve symptoms and quality of life. [12][13][14] One of the advantages of our technique is the ease of manipulation of the graft using the SpeedLock Hip anchor. It is a knotless anchor but allows rotation of the graft either away from or toward the femoral head by selective tensioning of the 2 sutures that are passed through the base of the graft and then into the anchor.…”
Section: Discussionmentioning
confidence: 99%